2019
DOI: 10.1101/679902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computational and experimental performance of CRISPR homing gene drive strategies with multiplexed gRNAs

Abstract: CRISPR homing gene drives potentially have the capacity for large-scale population modification or suppression. However, resistance alleles formed by the drives can prevent them from successfully spreading. Such alleles have been found to form at high rates in most studies, including those in both insects and mammals. One possible solution to this issue is the use of multiple guide RNAs (gRNAs), thus allowing cleavage by the drive even if resistance sequences are present at some of the gRNA target sequences. H… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
114
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(119 citation statements)
references
References 42 publications
2
114
3
Order By: Relevance
“…Limiting the rate at which undesired homology-directed repair events occur is critical for the design of an effective TARE drive, as they could lead to the formation of r1 resistance alleles if repair results in copying of the recoded region, but not the payload gene. However, previous studies have shown that the efficiency of homology-directed repair in homing drives already decreases bỹ 15% when the distance between cut sites and homology templates is~100 nucleotides on just one side 39 . For larger distances of 1000 nucleotides or more from cuts sites to repair template, drive efficiency in a multiple-gRNA homing drive fell over 50% 12 compared to similar drives with no distance between cut sites and templates [15][16][17] .…”
Section: Resultsmentioning
confidence: 95%
“…Limiting the rate at which undesired homology-directed repair events occur is critical for the design of an effective TARE drive, as they could lead to the formation of r1 resistance alleles if repair results in copying of the recoded region, but not the payload gene. However, previous studies have shown that the efficiency of homology-directed repair in homing drives already decreases bỹ 15% when the distance between cut sites and homology templates is~100 nucleotides on just one side 39 . For larger distances of 1000 nucleotides or more from cuts sites to repair template, drive efficiency in a multiple-gRNA homing drive fell over 50% 12 compared to similar drives with no distance between cut sites and templates [15][16][17] .…”
Section: Resultsmentioning
confidence: 95%
“…Recent research has raised concerns that natural polymorphisms could also hamper gene-drive spread in heterogeneous populations 33 . A proposed strategy to increase drive efficiency and work around resistant alleles or polymorphisms is to use multiple gRNAs to ensure cutting and lower the chances of an indel 17,34,35 . However, in such scenarios one cannot achieve perfect homology with all possible DNA ends generated when using multiple gRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…TADS suppression had the highest effectiveness of all drive types we tested. If suitable gene targets for such a system can be identified, this could enable the development of drives that can both minimize resistance alleles with multiplexed gRNAs (a useful strategy but with substantial limitations in homing-type drives 31 ) and achieve effective suppression over a large range of parameters.…”
Section: Discussionmentioning
confidence: 99%
“…A more severe problem is posed by "r1" resistance alleles, mutations that prevent targeting by gRNAs and preserve target gene function. However the formation rate of r1 alleles can be reduced by using multiple gRNAs 31 or a highlyconserved target site that cannot tolerate mutations 15 . In a recent experiment, a female fertility homing drive like the one we model here was successful in rapidly eliminating small cage populations of Anopheles gambiae 15 .…”
Section: Suppression Drive Strategiesmentioning
confidence: 99%